2007
DOI: 10.1038/sj.onc.1210382
|View full text |Cite
|
Sign up to set email alerts
|

The MN1-TEL myeloid leukemia-associated fusion protein has a dominant-negative effect on RAR-RXR-mediated transcription

Abstract: The translocation t(12;22)(p13;q11) creates an MN1-TEL fusion gene leading to acute myeloid leukemia. MN1 is a transcription coactivator of the retinoic acid and vitamin D receptors, and TEL (ETV6) is a member of the E26-transformation-specific family of transcription factors. In MN1-TEL, the transactivating domains of MN1 are combined with the DNA-binding domain of TEL. We show that MN1-TEL inhibits retinoic acid receptor (RAR)-mediated transcription, counteracts coactivators such as p160 and p300, and acts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…RAR/RXR recruits MN1 via the transcriptional coactivator p300/CBP. High expression of MN1 is associated with ATRA resistance in vitro and in human non-APL AML [14]. Heuser et al [13] also found that non-APL AML patients with low MN1 expression may benefit from treatment with ATRA.…”
mentioning
confidence: 96%
“…RAR/RXR recruits MN1 via the transcriptional coactivator p300/CBP. High expression of MN1 is associated with ATRA resistance in vitro and in human non-APL AML [14]. Heuser et al [13] also found that non-APL AML patients with low MN1 expression may benefit from treatment with ATRA.…”
mentioning
confidence: 96%
“…Exactly how MN1 contributes to leukemogenesis is still not fully understood. A dominant negative effect on RAR/TEL signaling has been described for the MN1-TEL fusion (11), but this mechanism may not apply to MN1 overexpression. Importantly, MN1 has little structural similarity to any other protein (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…These translocations can result in the chimeric fusion of MN1 and TEL, the partial disruption of TEL, or no disruption in these genes. The oncogenic activities of MN1-TEL include the upregulation of HOXA9 and the inhibition of RAR-RXR-mediated transcription (Kawagoe et al, 2005;van Wely et al, 2007). The biological significance of the partial disruption of TEL caused by t(12;22) is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The fusion protein of MN1-TEL has oncogenic activities through the upregulation of HOXA9 and the inhibition of RAR-RXR-mediated transcription (Kawagoe et al, 2005;van Wely et al, 2007). However, some patients with t(12;22) did not have a chimeric MN1-TEL, and the implications of t(12;22) lacking MN1-TEL are not understood.…”
Section: Introductionmentioning
confidence: 98%